Impact of Dividend Policy on Firm Performance: Evidence from Non-Financial Firms of Pakistan - Jatoi, Muhammad Zulqarnain; Rasheed, Abdul; Wahla, Khalil-Ur-Rehman (Pakistan Journal of Humanities and Social Sciences, 2023)
This study has aim to evaluate whether the policies of divided affects the performance of non-financial firms that are publically traded in Pakistan. Data was collected between 2010 and 2021 from the State Bank of Pakistan's website and through financial statement analysis of non-financial businesses.Certainly! According to the SPSS results, there is a noteworthy positive correlation between Return on Equity (ROE) and Dividend Policy. This implies that as Financial Leverage (FL), Dividend per Share (DPS), Earning per Share (EPS), and Dividend Payout Ratio (DPOR) increase, and the ROE also rises for all of the non-financial firms included in the study. Additionally, a significant positive connection between Dividend Policy (which includes all of the variables FL, EPS, DPS, and DPOR) and Return on Assets (ROA) was found.I can rephrase that for you! Therefore, this research provides evidence that Dividend Policieshave significant influence on Firms/Companies Performance.